The Effect of Motivation, Job Satisfaction, and Work Discipline on Employee Performance - Muhammad Rudiansyah (Almana : Jurnal Manajemen dan Bisnis, 2022)
The problems experienced by employees at Suzuki Finance Banjarmasin include decreased work motivation and job satisfaction which affect decreasing employee performance. One indication is the high level of absenteeism and tardiness that is increasing, which is one of the factors that is thought to be the cause of the decline in employee performance. The purpose of this study was to determine the effect of motivation, job satisfaction, and work discipline on employee performance, either simultaneously or partially, and also to determine the most dominant independent variable affecting employee performance. The population in this study was all employees of the Suzuki Finance Banjarmasin office. The research sample was 33 people using the census technique (saturated sampling) and analyzed by multiple linear regression data analysis technique using the SPSS-25 computer application. Based on the results of this study, it is known that simultaneously motivation, job satisfaction, and work discipline have a significant effect on employee performance, partially, only two variables, namely job satisfaction, and work discipline, have a significant effect on employee performance, job satisfaction has a dominant effect on employee performance.